Paediatric Nursing Skills Made Easy - Chan, K.G; Lee,, Shalin Wan Fei (Universiti Malaysia Sarawak (UNIMAS), 2017)
In our attempt to compile a book on essential procedures related to paediatric nursing, our goal is to provide a text that would be useful as a reference and guidelines with nursing students or even practicing paediatric nurses in mind. While there are other text books related to step-by-step nursing procedures, this particular publication addresses variations specifically on the care of hospitalized child common within the local context. This text with its focus on care provision to meet the unique needs of the hospitalized child would complement the other recommended nursing textbooks. At the beginning of each nursing procedure, we emphasize on importance of identification for the correct child, hand hygiene, consent and giving of clear information to the child as developmentally appropriate. The practice of family-centered care is integrated to encourage parental participation in meeting the needs of their hospitalized child. The introductory Chapter One outlines important General Principles related to correct patient identification, consent, hand hygiene, privacy and documentation which should be considered and applied when carrying out any nursing procedures on hospitalized children. Chapters Two to Twelve are procedural chapters. Each chapter contains of procedures with details on step-by-step procedural implementations as well as the explanations to rationalize each step. The requirements listed for each procedure summarizes the equipment and materials that should be gathered in readiness before starting the procedures. Key points of procedures to be alerted are also included. We are certain that information which is written in simple English as contained in this book would help to students’ understanding and learning. Thus, we have great hope it would contribute towards improving nursing students’ confidence in their delivery of care.